Implementation of Tensor Flow in Air Quality Monitoring Based on Artificial Intelligence - Rahardja, Untung; Aini, Qurotul; Manongga, Danny; Sembiring, Irwan; Girinzio, Iqbal Desam (Universitas Dharma Wacana, 2022)
Chemicals that cannot be controlled today can pollute resources and the environment. Common sources of pollutants are due to public transportation, cigarette smoke, volcanic activity that emits volcanic ash, factory smoke, forest fires, biogas, or carbon dioxide. The purpose of this paper is to monitor air quality, detect air and anticipate pollution levels. With the specified algorithms, three algorithms will be used to create a good and accurate model where four different gasses are predicted: carbon dioxide, sulfur dioxide, and nitrogen dioxide, in this paper, there are four algorithms used for the Air Qualification Index which are Support Vector Regression, Linear Regression, and Ensemble Gradient Boosted Decision Tree. This research also includes quantitative research which is hypothesized to be evaluated against Root Mean Squared Error, Mean Squared Error, and Mean Absolute error, depending on the performance of the measurements made by artificial intelligence, and the lower error value is selected. Based on the algorithm to be predicted in this air quality monitoring, there are 5 air pollutants like Carbon dioxide, Sulfur dioxide, and Nitrogen dioxide, and the sensors to be used are two sensors like PM2.5 and PM10 that can be predicted.